The effect of crisis on demography and employment in CEE countries - Lukács Gellérné, Éva; Mészáros, Árpád József; Pári, András (Frontiers in Political Science, 2025)
Europe faces the most challenging long-term demographic forecasts globally. Over the centuries, demographers have conducted extensive studies to uncover the drivers behind population trends, relying on theories such as demographic transitions and economic models. Europe is currently experiencing a pronounced migration trend coupled with declining birth rates and total fertility rates. Crises usually generate negative effects, as demonstrated by the greater than average decrease in birth rates and employment rates during the COVID period in Europe. Declining population trends have, and will continue to have, adverse effects on the labor market. To mitigate these detrimental impacts, the EU adopted important measures since 2009. Although the decline in the employment rate recovered quickly in the EU, demographic trends have not. In 2022, the European Commission also shifted its focus and introduced several initiatives aimed at improving demographic outcomes at EU level. Moreover, demography has emerged as an independent policy area, recognized as a key element of the triple transition and competitiveness. By contrast, Central and Eastern European (CEE) countries implemented active demographic policies much earlier, particularly after the 2008 economic crisis with registered success. However, in relative terms, crises have had a more significant impact on both demographics and the labor market in the CEE region. Labor market flexibility in the region does not sufficiently support demographic policies. This paper examines these trends and argues that a combined approach of enhancing labor market flexibility and supporting families is essential for alleviating the adverse demographic trends affecting Europe. It further argues that for CEE countries, due to their increased vulnerability, it is crucial to continue prioritizing demographic measures that support families and strengthen the labor market.